1996
DOI: 10.1016/0304-3959(96)03127-2
|View full text |Cite
|
Sign up to set email alerts
|

Is there a pathway in the posterior funiculus that signals visceral pain?

Abstract: The present report provides evidence that axons in the medial part of the posterior column at T10 convey ascending nociceptive signals from pelvic visceral organs. This evidence was obtained from human surgical case studies and histological verification of the lesion in one of these cases, along with neuroanatomical and neurophysiological findings in animal experiments. A restricted lesion in this area can virtually eliminate pelvic pain due to cancer. The results remain excellent even in cases in which somati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(107 citation statements)
references
References 89 publications
(98 reference statements)
5
100
0
2
Order By: Relevance
“…Bilateral projections of these systems exist in animals. 28 -30 The lemniscal system may also be involved, because it may take part in visceral nociceptive perception 2,31 ; however, there is no evidence that this pathway plays a role in cutaneous pain. The information processing to the cortex is slow and multisynaptic, as indicated by the delay between the stimulation application and the occurrence of painful sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral projections of these systems exist in animals. 28 -30 The lemniscal system may also be involved, because it may take part in visceral nociceptive perception 2,31 ; however, there is no evidence that this pathway plays a role in cutaneous pain. The information processing to the cortex is slow and multisynaptic, as indicated by the delay between the stimulation application and the occurrence of painful sensation.…”
Section: Discussionmentioning
confidence: 99%
“…This was also demonstrated in animal studies, in which dorsal column activity was observed in pelvic visceral nociception. 86 Initially, there was lack of evidence for the application of spinal cord stimulation for visceral and somatic pain, secondary to the belief that nociceptive pain could not be modulated via stimulation. Several initial studies have since demonstrated the benefit of SCS in abdominal visceral disease.…”
Section: Abdominal and Visceral Pain Syndromesmentioning
confidence: 99%
“…The dorsal column pathway consists of direct afferent projections from large-diameter Aβ fibers and projections from post-synaptic dorsal column (PSDC) neurons Hendry et al 1999;Palecek, 2004;Willis and Coggeshall, 2004). It is well established that the PSDC neurons mediate visceral pain (Al-Chaer et al 1996a,b;Hirshberg et al 1996;Houghton et al 1997;Nauta et al 1997;Houghton et al 2001). For example, the physiologic responses of PSDC neurons to colorectal distension are opioid-sensitive and behavioral responses to noxious visceral stimuli are blocked by lesions of the dorsal columns (Al-Chaer et al 1996a;Houghton et al 2001;Palecek et al 2002).…”
Section: Introductionmentioning
confidence: 99%